2002
DOI: 10.1590/s0004-28032002000100007
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in advanced colorectal adenocarcinoma with special reference to tumoral invasion

Abstract: -Background -Angiogenesis is a crucial step in tumor growth and progression. Its quantification by microvessel counting has a prognostic value in several types of malignancies and recently has been appraised in gastrointestinal tumors. Aim -To assess the prognostisc significance of microvessel quantification in colorectal carcinomas, studying its association with hematogenous metastases, survival and clinicopathological variables such as size, histologic differentiation and depth of tumoral invasion. Patients/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
2
12
0
2
Order By: Relevance
“…Many studies report a relationship between increased MVD and decreased survival (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Some investigators have reported that MVD is not a prognostic factor in colorectal carcinomas (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report a relationship between increased MVD and decreased survival (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Some investigators have reported that MVD is not a prognostic factor in colorectal carcinomas (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…There are a lot of reports showing that the higher microvessel density is associated with the metastases development, poor prognosis and life expectancy shortage in colorectal cancer patients (Choi et al, 1998;Engel et al, 1996;Frank et al, 1995;Galindo, 2000;Giatromanolaki et al, 2006Koukourakis et al, 2005Li et al, 2003Rasheeda S. et al, 2009;Sternfeld et al, 1999, Takahashi et al, 1997Takebayashi et al, 1996;Tanigawa et al, 1997;Tomisaki et al, 1996;Uribarrena et al, 2009;White et al, 2002). However, there are conflicting results regarding the prognostic value of tumour MVD (Abdala et al, 1999, Bossi et al, 1995Ellis at al., 1998;Pietra et al, 2000;Tarta et al, 2002). In the current study the microvessel counts are high (163/mm² on average), which confirms the assumption that the rectal carcinoma is strongly dependent on angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, angiogenesis is considered to correlate with carcinoma development 20–22 . In the esophageal field it has been reported that intrapapillary capillary loop detected using magnified observation is a useful indicator for invasion depth diagnosis for superficial esophageal carcinoma 23 .…”
Section: Discussionmentioning
confidence: 99%